Konflik Batin dan Kebahagiaan Tokoh Malla dalam Cerita Pendek “Kebahagiaan yang Membunuh” Karya Atta Verin Kajian Psikologis - Badriah Badriah; Nori Anggraini (Lembaga Pengembangan Kinerja Dosen, 2026)
Literature is not only a source of entertainment, but also a tool for contemplating human life that is full of internal conflicts and psychological issues. Short stories as a type of literature often present the realities of life in a concise yet meaningful way, making them interesting to analyze with a variety of scientific methods. This research focuses on the short story